Pleasure, impulse, compulsion, and rationality in the behavior of young consumers in the context of contemporary challenges and current events - Perchla-Włosik, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
In modern societies, significant changes are taking place in the sphere of consumption. Consumption is no longer just a way of satisfying needs. Sometimes it can also be about experiencing pleasure (also on impulse) or relieving tension. A characteristic behavior of pleasure consumers is the spontaneous (impulsive) purchase of goods that are attractive to them. At the same time, impulsive purchases differ from rationalized purchases in that the decision to purchase a given product is made quickly and usually without deeper reflection. The purpose of this article is to try to answer the question, what is the essence of purchasing decisions in the face of the challenges of the modern world, such as the COVID-19 pandemic, the war in Ukraine and inflation? What are the shopping habits of young consumers, especially in relation to their emotional, psychological, social, and economic spheres? In light of these challenges, can one notice any adaptation strategies, “survival” strategies, rationalization of behavior, or, on the contrary, will the orientation towards pleasure, compulsive shopping, or impulse purchases dominate? The subject of this article is the consumer behavior of young people, perceived as a series of reactions to various stimuli — instincts, emotions — that inspire and mobilize them to satisfy their needs. The answers to the questions posed above were obtained by analyzing the data obtained through qualitative research using the technique of focus group interviews.
Keywords: consumer behavior; pleasure consumer; compulsive and impulsive behavior; COVID-19; war in Ukraine; inflation